A semi-empirical potential energy surface and line list for H216O extending into the near-ultraviolet - E. K. Conway; E. K. Conway; I. E. Gordon; J. Tennyson; O. L. Polyansky; S. N. Yurchenko; K. Chance (Atmospheric Chemistry and Physics, 2020)
Accurate reference spectroscopic information for the water molecule from the microwave to the near-ultraviolet is of paramount importance in atmospheric research. A semi-empirical potential energy surface for the ground electronic state of <msubsup>H216</msubsup>O<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="28pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="11c6760be345254f33f3f3e4de36fc5b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-10015-2020-ie00004.svg" width="28pt" height="17pt" src="acp-20-10015-2020-ie00004.png"/></svg:svg> has been created by refining almost 4000 experimentally determined energy levels. These states extend into regions with large values of rotational and vibrational excitation. For all states considered in our refinement procedure, which extend to 37 000 cm−1 and J=20 (total angular momentum), the average root-mean-square deviation is approximately 0.05 cm−1. This potential energy surface offers significant improvements when compared to recent models by accurately predicting states possessing high values of J. This feature will offer significant improvements in calculated line positions for high-temperature spectra where transitions between high J states become more prominent. Combining this potential with the latest dipole moment surface for water vapour, a line list has been calculated which extends reliably to 37 000 cm−1. Obtaining reliable results in the ultraviolet is of special importance as it is a challenging spectral region for the water molecule both experimentally and theoretically. Comparisons are made against several experimental sources of cross sections in the near-ultraviolet and discrepancies are observed. In the near-ultraviolet our calculations are in agreement with recent atmospheric retrievals and the upper limit obtained using broadband spectroscopy by Wilson et al. (2016, p. 194), but they do not support recent suggestions of very strong absorption in this region.